Obinnas advice - Ifoegbuna, Ifeanyi (Literamed Publications Nigeria Ltd, 2008)
Obinna is respected throughout his village because of his intelligence and strength. His advice to Dan and May to constantly visit the doctor whenever their child develops a flu came as a result of his education which he intends to use to benefit his people.
Keywords: Fiction; Health; Juvenile Literature